2002
DOI: 10.1053/jlts.2002.35544
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the results of liver transplantation for adults with severe hepatopulmonary syndrome

Abstract: The hepatopulmonary syndrome (HPS), consisting of elevated alveolar-arterial oxygen gradient and intrapulmonary vascular abnormalities in the presence of advanced liver disease, is associated with high mortality. Liver transplantation (LT) has been used for the treatment of HPS; however, the success of LT for the treatment of HPS is not uniformly documented. We reviewed our experience over a 5-year period and identified eight adult patients with incapacitating respiratory symptoms compatible with HPS. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 30 publications
(20 reference statements)
7
26
0
9
Order By: Relevance
“…Underscoring the role of schistosomiasis-related PH (without associated cirrhosis) in the etiology studies. (20) According to the 2004 arterial blood gas standards for the diagnosis of HPS, (1) the frequency of the syndrome in the present study was 45.5%.…”
Section: Discussionsupporting
confidence: 43%
“…Underscoring the role of schistosomiasis-related PH (without associated cirrhosis) in the etiology studies. (20) According to the 2004 arterial blood gas standards for the diagnosis of HPS, (1) the frequency of the syndrome in the present study was 45.5%.…”
Section: Discussionsupporting
confidence: 43%
“…18,22 However, each HPS case that is considered severe should be analyzed individually because of the high morbidity and mor-tality rates associated with this condition, both during surgery and during the postoperative period. 5,14,47 Without liver transplantation, the long-term mortality rate is higher among cirrhotic patients with HPS than among those without HPS. 13,90 Prospective analysis among candidates for liver transplantation has demonstrated significantly lower mean survival among patients with HPS than among those without HPS (4.8 months and 35.3 months respectively; P = 0.005) when they do not receive a transplant, even compared with the same classification of Child-Pugh score (0.26 months and 3.82 months respectively; P = 0.01).…”
Section: Hps Treatment and Prognosismentioning
confidence: 99%
“…13 This is likely to have been due to the rapid progression of hypoxemia in the patients with HPS and the mean annual decline in PaO 2 of approximately 5 mmHg. 13 It has been shown that, following transplantation, the oxygen saturation improves, the oxygen dependence of HPS patients is resolved 47 and there are similar mortality rates among patients with and without HPS. 13 These findings confirm the changes to the course of HPS and consequent prognosis for such patients that transplantation causes.…”
Section: Hps Treatment and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…27 Hypoxemia can be corrected as early as 6-12 months after OLT, 9,30 although the time taken for hypoxemia to reverse can be longer in patients who have severe HPS. An increased recovery time is observed when the patient has a preoperative PaO 2 ≤52 mmHg, a preoperative AaPO 2 ≥66 mmHg, is >48 years of age, or if the liver disease is a result of alcohol abuse.…”
Section: Reversibility Of Hepatopulmonary Syndromementioning
confidence: 99%